2004
DOI: 10.1096/fj.04-2321fje
|View full text |Cite
|
Sign up to set email alerts
|

Transcription profiling analysis of the mechanisms of vaccine‐induced protection against H. pylori

Abstract: Development of a vaccine against H. pylori is regarded as desirable alternative to the current antibiotic therapy regimens. Mice immunized with an attenuated recombinant Salmonella typhimurium expressing H. pylori urease subunits A&B have dramatically reduced bacterial loads after a single dose. The mechanism(s) of protection against this largely extra-cellular pathogen are not fully understood. The aim of this study was to identify genes that were regulated specifically in response to immunization, in order t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
45
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(50 citation statements)
references
References 34 publications
4
45
1
Order By: Relevance
“…2B); a similar trend was observed in the antrum region although this did not reach statistical significance. Carriervaccinated mice had similar gastritis scores to that of vaccinated mice, in keeping with our previous observations [25].The increased gastritis in vaccinated mice is known to result at least in part from influx of CD4 1 cells. We therefore determined the total numbers of CD4 1 cells (isolated from the stomachs of five mice at each time point) infiltrating the mucosa over time.…”
supporting
confidence: 91%
See 4 more Smart Citations
“…2B); a similar trend was observed in the antrum region although this did not reach statistical significance. Carriervaccinated mice had similar gastritis scores to that of vaccinated mice, in keeping with our previous observations [25].The increased gastritis in vaccinated mice is known to result at least in part from influx of CD4 1 cells. We therefore determined the total numbers of CD4 1 cells (isolated from the stomachs of five mice at each time point) infiltrating the mucosa over time.…”
supporting
confidence: 91%
“…This reduction was modest (1.8-fold) on day 3, although statistically significant (po0.04), and became substantial by days 7 and 21 (ten-fold, po0.004 and 100-fold, po0.0001, respectively). Analysis at later time points (day 35 and day 70, 1 year) revealed that the degree of protection did not further increase after day 21 (data not shown) [24,25]. It is noteworthy that carrier-vaccinated C57BL/6 mice also exhibited reductions in H. pylori colonisation compared with the control non-vaccinated mice ('carrier effect'), and this reduction was statistically significant at both 7 and 21 days post challenge (po0.003).…”
mentioning
confidence: 92%
See 3 more Smart Citations